2000
DOI: 10.1046/j.1442-200x.2000.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Can zinc deficiency be used as a marker for the diagnosis of celiac disease in Turkish children with short stature?

Abstract: These results indicate that zinc deficiency is an important problem in CD children with short stature; however, plasma zinc levels are not useful as a screening test for selecting patients for jejunal biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…37 Growth retardation also occurs in zinc deficiency in CD as in present study. 38 We found that serum zinc level is the most reducing one in classical CD. There is a publication claims that GI symptoms are more common in male while the other claims that there is not any difference among males and females according to GI symptoms.…”
mentioning
confidence: 64%
“…37 Growth retardation also occurs in zinc deficiency in CD as in present study. 38 We found that serum zinc level is the most reducing one in classical CD. There is a publication claims that GI symptoms are more common in male while the other claims that there is not any difference among males and females according to GI symptoms.…”
mentioning
confidence: 64%
“…Zinc deficiency has been found in 67% of untreated adult patients. Notably, all three studies reporting zinc levels in pediatric patients with active disease have found levels below the reference value in more than half of the patients, and a prospective randomized controlled trial conducted by Rawal et al even found zinc deficiency to be present in more than 70% of patients [37,47,50].…”
Section: Nutritional Deficiencies At Moment Of Diagnosis In Untreatedmentioning
confidence: 99%
“…Two other important minerals that can cause complications in CD patients when deficient, are zinc and magnesium. As summarized earlier, zinc deficiency is highly prevalent at diagnosis in pediatric and adult CD patient and seems to restore insufficiently when on a GFD [18,24,[34][35][36][37]43,47,50,89].…”
Section: Comorbidities Potentially Related To Nutrient Deficiencies Imentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings were not consistent with those of other authors researchers as Jameson (24), who reported a correlation between zinc deficiency and the severity of villous atrophy in adults. In addition, studies (25,26) have concluded that serum zinc concentrations were low in newly diagnosed and severely malnourished children with CD. The authors speculated that some of the symptoms of CD (eg, anorexia and reduced growth rate) may be related, in part, to zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%